Overview of Leaders' Perceptions of the Gender Microaggression on Women in the Workplace - Putu Cinthya Citra Iswari; Alice Whita Savira; Endah Mastuti (Philanthropy: Journal of Psychology, 2023)
This study aims to explore leaders' perceptions of gender microaggression impacts on women in the workplace. The role of the leader in reducing or even increasing gender microaggression in the workplace is adequately central that the leader's perception, especially their opinion of gender microaggression, will describe the leader’s decision if the female employees at the workplace obtain gender microaggression. This study used a qualitative research design with data analysis methods, particularly thematic analysis with an inductive approach. Data were collected using semi-structured interviews and short stories (vignettes) for each participant. The results of the study stated that both microinsults & microinvalidation have positive impacts and microassaults have negative impacts on women. Overall, the participants did not realize that gender microaggression could lead to some negative impacts on women with the result that the participants felt no obligation to execute any intervention in reducing gender microaggression.Keywords: gender microaggressions, impact, leader